2021
DOI: 10.1108/vjikms-10-2020-0185
|View full text |Cite
|
Sign up to set email alerts
|

Understanding knowledge hiding in the context of virtual workplaces

Abstract: Purpose This paper aims to explore the implications of virtual work arrangements on employee knowledge hiding (KH) behaviour and the different strategies of KH used by employees in these arrangements. Design/methodology/approach Following a grounded theory approach to understanding KH, 21 semi-structured in-depth interviews were conducted with employees engaged in virtual working setups. The data collected from these informants were then analysed using qualitative methods. Findings The study revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…The reasons given being: 1) insecurity -lack of a structured KS process, fear of losing recognition for their knowledge, protecting themselves (3 interviewees); 2) digital burnout -tiredness, lack of time, to avoid generating more work (3 interviewees); 3) distrust -not knowing people well, not knowing who to trust (1 interviewee). These findings considering communication managers in companies in Brazil were also identified by Choudhary and Mishra (2021) in relation to employees in consulting companies in India.…”
Section: Motivations For Khimentioning
confidence: 63%
See 3 more Smart Citations
“…The reasons given being: 1) insecurity -lack of a structured KS process, fear of losing recognition for their knowledge, protecting themselves (3 interviewees); 2) digital burnout -tiredness, lack of time, to avoid generating more work (3 interviewees); 3) distrust -not knowing people well, not knowing who to trust (1 interviewee). These findings considering communication managers in companies in Brazil were also identified by Choudhary and Mishra (2021) in relation to employees in consulting companies in India.…”
Section: Motivations For Khimentioning
confidence: 63%
“…These motivations were identified in different contexts, for example, service companies, and universities, among others. However, the only study looking at the context of remote work, from Choudhary and Mishra (2021), identified the following motivations for KHi in a remote work environment by consultants: competition, conflict, poor personal relations, insecurity, organizational politics, distrust, ease of hiding, lack of informal communication, digital burnout, and loss of control. Distrust being an example of a motivation identified in both remote and face-to-face work.…”
Section: Knowledge Sharing and Knowledge Hidingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, each of the three approaches is apt to achieve distinctive theoretical contributions given their methodological characteristics. In fact, some recent empirical works aiming at theoretical modeling that supports knowledge hiding behavior follow such flexibility in coding (Choudhary & Mishra, 2021;Jha & Varkkey, 2018;Liu et al, 2020). Jha and Varkkey (2018), in their study focused on understanding conditions leading to knowledge hiding in pharmaceutical companies, follow a coding protocol using the three approaches.…”
Section: Figure 2 Coding Framework Of Classic Gt (Adapted From Holton...mentioning
confidence: 99%